Russian heritage language development in narrative contexts: Evidence from pre- and primary-school children in Norway, Germany, and the UK - Rodina, Yulia; Bogoyavlenskaya, Alexandra; Mitrofanova, Natalia; Westergaard, Marit (Frontiers in Psychology, 2023)
The present study aims at obtaining a comprehensive picture of language development in Russian heritage language (RHL) by bringing together evidence from previous investigations focusing on morphosyntax and global accent as well as from a newly conducted analysis of a less-studied domain – lexical development. Our investigation is based on a narrative sample of 143 pre- and primary school bilinguals acquiring RHL in Norway, Germany, and the United Kingdom. We performed a multiple-way analysis of lexical production in RHL across the different national contexts, across both languages (heritage and societal), also comparing bilinguals and monolinguals. The results revealed a clear and steady increase with age in narrative length and lexical diversity for all bilingual groups in both of their languages. The variation in lexical productivity as well as the differences between the bilingual groups and between bilinguals and monolinguals were attributed to input factors with language exposure in the home and age of starting preschool as the major predictors. We conclude that, overall, the results from lexical, grammatical, and phonological acquisition in RHL support the view that having longer exclusive or uninterrupted exposure to a heritage language in early childhood is beneficial for its development across domains.